Role of ς(B) in Heat, Ethanol, Acid, and Oxidative Stress Resistance and during Carbon Starvation in Listeria monocytogenes - Ferreira, Adriana (American Society for Microbiology, 2001)
To determine the contribution of sigma B (ς(B)) to survival of stationary-phase Listeria monocytogenes cells following exposure to environmental stresses, we compared the viability of strain 10403S with that of an isogenic nonpolar sigB null mutant strain after exposure to heat (50°C), ethanol (16.5%), or acid (pH 2.5). Strain viabilities were also determined under the same conditions in cultures that had been previously exposed to sublethal levels of the same stresses (45°C, 5% ethanol, or pH 4.5). The ΔsigB and wild-type strains had similar viabilities following exposure to ethanol and heat, but the ΔsigB strain was almost 10,000-fold more susceptible to lethal acid stress than its parent strain. However, a 1-h preexposure to pH 4.5 yielded a 1,000-fold improvement in viability for the ΔsigB strain. These results suggest the existence in L. monocytogenes of both a ς(B)-dependent mechanism and a pH-dependent mechanism for acid resistance in the stationary phase. ς(B) contributed to resistance to both oxidative stress and carbon starvation in L. monocytogenes. The ΔsigB strain was 100-fold more sensitive to 13.8 mM cumene hydroperoxide than the wild-type strain. Following glucose depletion, the ΔsigB strain lost viability more rapidly than the parent strain. ς(B) contributions to viability during carbon starvation and to acid resistance and oxidative stress resistance support the hypothesis that ς(B) plays a role in protecting L. monocytogenes against environmental adversities.